PENGARUH STRUKTUR AUDIT, PROFESIONALISME, DAN KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR - Elya Zulfa Diani, 15.05.52.0254; Meita, Rahmawati (Students' Journal of Accounting and Banking, 2019)
This research is motivated by the demands of auditors to have extensive knowledge, especially in the field of auditing. So that the auditor can produce audit products that can be relied on by the user, as well as competition from various factors that cause the auditor to maintain his position on the organization. The purpose of this reseach aimed to examine and analyzes the effect of audit structure, professionalism, and organizational commitment on auditor performance. The population which became the object of this study is the auditor who works for the Public Accounting Firm in Semarang City, which registered with the Institute Akuntan Publik Indonesia (IAPI) in February 2018. The research use Convenience Sampling method. The sample in this study included 13 KAP with 66 respondents. Data analysis used a linear regression models with the help of the SPSS 16.0 program. The results of this study indicate that audit structure variables have a significant negative effect on auditor performance, professionalism and organizational commitment has a significant positive effect on auditor performance.